A note on the price variable - Bliss, Christopher (International Food Policy Research Institute, 1985)
Dharm Narain's concern with the effect of absolute prices on poverty poses a challenge to orthodox beliefs. Poverty is a "real" phenomenon that, according to a simple view of the matter, should not be importantly influenced by "nominal" values. As Amartya Sen remarks, the really intereested feature of Dharm Narain's formulation relates, not to time, but to the use of price index. I agree, but I also think that there is much truth in the orthodox view that poverty eventually depends on the "real" economy. Therefore, I am surprised that it can be so growssly set aside, in a time-series application, with such apparent success.